Snake Venomics of the Central American Rattlesnake Crotalus simus and the South American Crotalus durissus Complex Points to Neurotoxicity as an Adaptive Paedomorphic Trend along Crotalus Dispersal in South America - Calvete, Juan J; Sanz, Libia; Cid, Pedro; de la Torre, Pilar; Flores-Díaz, Marietta; Dos Santos, M. Cristina; Borges, Adolfo; Bremo, Adolfo; Angulo, Yamileth; Lomonte, Bruno; Alape-Girón, Alberto; Gutiérrez, José María (Journal of proteome research, 2010)
We report a comparative venomic and antivenomic characterization of the venoms of newborn and adult specimens of the Central American rattlesnake, Crotalus simus, and of the subspecies cumanensis, durissus, ruruima, and terrificus of South American Crotalus durissus. Neonate and adult C. simus share about 50% of their venom proteome. The venom proteome of 6-week-old C. simus is predominantly made of the neurotoxic heterodimeric phospholipase A2 (PLA2 crotoxin) (55.9%) and serine proteinases (36%), whereas snake venom Zn2+-metalloproteinases (SVMPs), exclusively of class PIII, represent only 2% of the total venom proteins. In marked contrast, venom from adult C. simus comprises toxins from 7 protein families. A large proportion (71.7%) of these toxins are SVMPs, two-thirds of which belong to the PIII class. These toxin profiles correlate well with the overall biochemical and pharmacological features of venoms from adult (hemorrhagic) and newborn (neurotoxic) C. simus specimens. The venoms of the South American Crotalus subspecies belong to one of two distinct phenotypes. C. d. cumanensis exhibits high levels of SVMPs and low lethal potency (LD50), whereas C. d. subspecies terrificus, ruruima, and durissus have low SVMP activity and high neurotoxicity to mice. Their overall toxin compositions explain the outcome of envenomation by these species. Further, in all C. simus and C. durissus venoms, the concentration of neurotoxins (crotoxin and crotamine) is directly related with lethal activity, whereas lethality and metalloproteinase activity show an inverse relationship. The similar venom toxin profiles of newborn C. simus and adult C. durissus terrificus, ruruima, and durissus subspecies strongly suggests that the South American taxa have retained juvenile venom characteristics in the adult form (paedomorphism) along their North−South stepping-stone dispersal. The driving force behind paedomorphism is often competition or predation pressure. The increased concentration of the neurotoxins crotoxin and crotamine in South American rattlesnake venoms strongly argues that the gain of neurotoxicity and lethal venom activities to mammals may have represented the key axis along which overall venom toxicity has evolved during Crotalus durissus invasion of South America. The paedomorphic trend is supported by a decreasing LNC (lethal neurotoxicity coefficient, defined as the ratio between the average LD50 of the venom and the crotoxin + crotamine concentration) along the North−South axis, coincident with the evolutionary dispersal pattern of the Neotropical rattlesnakes. The indistinguisable immunoreactivity patterns of Costa Rican and Venezuelan polyvalent antivenoms toward C. simus and C. durissus venoms strongly suggest the possibility of using these antivenoms indistinctly for the management of snakebites by adult C. simus and by certain C. d. cumanensis populations exhibiting a hemorrhagic venom phenotype. The antivenomic results also explain why the antivenoms effectively neutralize the hemorrhagic activity of adult C. simus venoms but does not protect against adult C. durissus sp. and newborn C. simus envenomations. The identification of evolutionary trends among tropical Crotalus, as reported here, may have an impact in defining the mixture of venoms for immunization to produce an effective pan-American anti-Crotalus antivenom.